Beyond the Smoke and Mirrors Graphic Health Warnings and the Freedom of Expression of Tobacco Companies (2014)
In presenting the nature of regulations in the Philippine tobacco industry, the article discusses the proper role of government intervention in and the extent of protection that must be accorded to commercial speech. To assess the standard of protection, US jurisprudence offers two options: the Strict Scrutiny test from Wooly v. Maynard, and the Intermediate Scrutiny test in Central Hudson Gas & Electric Corp. v. Public Service Commission. Here, the article applies Central Hudson to previously-filed bills that would have compelled the use of graphic health warnings, in hopes of aiding future legislators in drafting similar measures. The article also espouses the soft-paternalism framework in approaching tobacco control, arguing that this is appropriate because individuals display behavioral and cognitive biases, including "self control problems" and systematic mispredictions about the costs and benefits of choices." The framework thus serves to reconcile the protection of freedom of speech with the responsibility of the State to safeguard public health.
Keywords: The Graphic Health Warnings on Tobacco Products Law; Freedom of expression